2021
DOI: 10.1007/s10461-021-03306-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Engagement in HIV Care Among Transgender Women of Color in the United States of America

Abstract: HIV prevalence among transgender women of color (TWC) in the United States of America is high. We enrolled TWC living with HIV (N = 858) to evaluate 1nine HIV care interventions. We examined factors associated with four outcomes at enrollment: linkage to care, ever being on antiretroviral treatment, retention in care and viral suppression. The sample was 49% Hispanic/Latino, 42% Black; average age was 37 years; 77% were ever linked to care, 36% were ever on treatment, 22% were retained in care, and 36% were vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…This finding is consistent with studies that have found that receiving quality, affirming health services in a welcoming and trans-friendly environment was associated with increased engagement in sexual health services 42 and where trans clients can connect and derive support from one another as well as from their providers. 64,65 Gender affirmation 43 and healthcare empowerment 66 have been shown to moderate the deleterious impact that trans-related discrimination has on rates of viral suppression among Black and Latinx TGW with HIV. 67 Guidelines for gender-affirming care of trans and non-binary people include ensuring a safe and welcoming environment by utilizing a patient's gender identity, and taking a gender-affirming approach for any physical exams.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with studies that have found that receiving quality, affirming health services in a welcoming and trans-friendly environment was associated with increased engagement in sexual health services 42 and where trans clients can connect and derive support from one another as well as from their providers. 64,65 Gender affirmation 43 and healthcare empowerment 66 have been shown to moderate the deleterious impact that trans-related discrimination has on rates of viral suppression among Black and Latinx TGW with HIV. 67 Guidelines for gender-affirming care of trans and non-binary people include ensuring a safe and welcoming environment by utilizing a patient's gender identity, and taking a gender-affirming approach for any physical exams.…”
Section: Discussionmentioning
confidence: 99%
“…7 As with other populations, trans women living with HIV who are suboptimally engaged in HIV care are at increased risk for negative health outcomes, such as unsuppressed viral load and increased risk of HIV transmission. 3,8…”
Section: Introductionmentioning
confidence: 99%
“…2 Furthermore, trans women living with HIV exhibit suboptimal advancement through the HIV care continuum. 3 Compared with other groups, trans women living with HIV are less likely to be retained in HIV care 3 and receive antiretroviral therapy (ART) 4 ; trans women on ART demonstrate lower levels of adherence 5 and higher viral loads. 6 Furthermore, trans women report less confidence in their ability to integrate treatment regimens into their daily lives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations